Chronic Obstructive Pulmonary Disease and Work: The Continuing Narrative - Fishwick, David; Barber, Chris; Wiggans, Ruth (Seminars in Respiratory and Critical Care Medicine, 2023)
It has long been recognized that harmful inhaled workplace exposures can contribute to the development of chronic obstructive pulmonary disease (COPD). This article, intended for the clinician, summarizes some of this evidence and some areas of controversy. Current estimates based on pooled epidemiological analyses of population-based studies identify that approximately 14% of the burden of COPD (and 13% of the burden of chronic bronchitis) is attributable to such exposures. In addition to these approaches, various studies implicate specific exposures as contributing. Certain of these relating to cadmium, coal, and respirable crystalline silica are discussed in more detail. Despite this amassed evidence to date supporting associations between COPD and workplace exposures, there have been surprisingly few studies that have attempted to assess the attribution by experts of an occupational cause in cases of COPD. One study, using hypothetical cases of COPD, noted that while expert physicians were willing to make such an occupational link, this was only likely in cases with light smoking histories and a priori defined heavy occupational exposures. Relatively recent data relating to computed tomography (CT) scan appearances may give the clinician a further guide. Several studies from populations have now linked potentially harmful occupational exposures specifically with the presence of emphysema on CT scanning. It will be of interest to see if this finding, along with other clinical attributes of cases such as smoking and family histories, exclusion of asthma, genetic data, and the nature of workplace exposures, will increase the future diagnosis by clinicians of occupational COPD. In the interim, while better diagnostic approaches are developed, we suggest that consideration of an occupational cause is an important part of the clinical investigation of cases of COPD. Finally, we suggest that evidence-based workplace preventive strategies for occupational COPD should be informed by knowledge of which exposures are most important to reduce, and whether and when intervention to reduce exposure at an individual worker level is warranted.
Keywords: chronic obstructive pulmonary disease; occupation; work; vapors; gases; dust; emphysema; attribution